Health system reform and the role of field sites based upon demographic and health surveillance - S.M Tollman; A.B Zwi (The World Health Organization, 2000)
Field sites for demographic and health surveillance have made well-recognized contributions to the evaluation of new or untested interventions, largely through efficacy trials involving new technologies or the delivery of selected services, e.g. vaccines, oral rehydration therapy and alternative contraceptive methods. Their role in health system reform, whether national or international, has, however, proved considerably more limited. The present article explores the characteristics and defining features of such field sites in low-income and middle-income countries and argues that many currently active sites have a largely untapped potential for contributing substantially to national and subnational health development. Since the populations covered by these sites often correspond with the boundaries of districts or subdistricts, the strategic use of information generated by demographic surveillance can inform the decentralization efforts of national and provincial health authorities. Among the areas of particular importance are the following: making population-based information available and providing an information resource; evaluating programmes and interventions; and developing applications to policy and practice. The question is posed as to whether their potential contribution to health system reform justifies arguing for adaptations to these field sites and expanded investment in them.